Factors associated with mortality of pediatric sepsis patients at the pediatric intensive care unit in a low-resource setting - Desy Rusmawatiningtyas; Arini Rahmawati; Firdian Makrufardi; Nurul Mardhiah; Indah Kartika Murni; Cuno S. P. M. Uiterwaal; Ary I. Savitri; Intan Fatah Kumara; Nurnaningsih (BMC, 2021)
Abstract Background Sepsis is the leading cause of death worldwide in pediatric populations. Studies in low-resource settings showed that the majority of pediatric patients with sepsis still have a high mortality rate. Methods We retrospectively collected records from 2014 to 2019 of patients who had been diagnosed with sepsis and admitted to PICU in our tertiary hospital. Cox proportional hazard regression modeling was used to evaluate associations between patient characteristics and mortality. Results Overall, 665 patients were enrolled in this study, with 364 (54.7%) boys and 301 (46.3%) girls. As many as 385 patients (57.9%) died during the study period. The median age of patients admitted to PICU were 1.8 years old with interquartile range (IQR) ±8.36 years and the median length of stay was 144 h (1-1896 h). More than half 391 patients (58.8%) had a good nutritional status. Higher risk of mortality in PICU was associated fluid overload percentage of > 10% (HR 9.6, 95% CI: 7.4-12.6), the need of mechanical ventilation support (HR 2.7, 95% CI: 1.6-4.6), vasoactive drugs (HR 1.5, 95% CI: 1.2-2.0) and the presence of congenital anomaly (HR 1.4, 95% CI: 1.0-1.9). On the contrary, cerebral palsy (HR 0.3, 95% CI: 0.1-0.5) and post-operative patients (HR 0.4, 95% CI: 0.3-0.6) had lower mortality. Conclusion PICU mortality in pediatric patients with sepsis is associated with fluid overload percentage of > 10%, the need for mechanical ventilation support, the need of vasoactive drugs, and the presence of congenital anomaly. In septic patients in PICU, those with cerebral palsy and admitted for post-operative care had better survival.